(untitled) (Medical Forum Monthly, 2024)
Objective: The study objectives to assess the impact of deproteinization with 5.25% sodium hypochlorite (NaOCl) before acid etching on the shear bond strength of orthodontic brackets adhered to fluorosed teeth. Study Design: Randomized clinical trial study Place and Duration of Study: This study was conducted at the Orthodontic Department of the Nishtar Institute of dentistry, Multan from June 2020 to Dec 2020. Methods: The included 60 fluorosed teeth were collected in 6 months. These premolars were extracted for orthodontic purposes from patients seeking fixed orthodontic treatment at the Department of Orthodontics. Upon completion of the required sample, the 60 teeth were divided into two groups consisting of 30 teeth each. In the control group (Group I), brackets were bonded to 20 teeth using composite resin without prior deproteinization, and the bonding process involved etching the teeth with 37% phosphoric acid. In the experimental group (Group II), brackets and fluorosed teeth were bonded after 5.25% NaOCl deproteinization using composite resin. Results: The mean megapascals (MPa) in Group I and Group II was 9.59±1.06 and 13.34±2.58, respectively. MPa was higher in Group II than the Group I, and this difference was statistically significant, (p<0.001). (Table. I).The modified ARI score 3 was most common in Group II and Group I, 9 (60.0%) and 6 (40.0%), respectively.(p=0.748). Conclusion: Prior to acid etching, the use of 5.25% NaOCl for deproteinization significantly enhances the shear bond strength of brackets adhered to fluorosed teeth, offering a convenient and effective option in orthodontic bonding procedures for such cases.